Effectiveness of photodynamic therapy on the treatment of chronic periodontitis: a systematic review during 2008–2023 - Mahdizade Ari, Marzie; Amirmozafari, Nour; Atieh Darbandi; Afifirad, Roghayeh; Asadollahi, Parisa; Irajian, Gholamreza (Frontiers in Chemistry, 2024)
The Objective: This study investigated the effect of photodynamic therapy on chronic periodontitis patients, and then evaluated the microbial, immunological, periodontal and clinical outcomes. The significant effects of photodynamic therapy obtained by in vitro and in vivo studies, made it a popular treatment for periodontal diseases in recent years. In comparison to root and scale planning, photodynamic therapy as a novel bactericidal strategy is stronger, faster, and less expensive. Method: This study registered on PROSPERO (CRD42021267008) and retrieved fifty-three randomized controlled trials (RCTs) by search in nine databases (Medline, Embase, Scopus, Open gray, Google Scholar, ProQuest, the Cochrane library, Web of sciences, and Clinical gov) from 2008 to 2023. Out of 721 records through database searches following title and full text analyzing, and excluding duplicate and irrelevance publications, finally 53 articles were included in this systematic review. Fifty out of fifty-three eligible studies fulfilled all of the criteria in the Joanna Briggs Institute (JBI's) Checklist for RCTs; the rest met nine to twelve criteria which were considered high quality.Results: Present study showed that photodynamic therapy in adjunct to root and to scale planning has the potential to improve periodontal parameters such as clinical attachment loss gain and decrease in bleeding on probing, probing pocket depth. Also, photodynamic therapy decreases the rate of periodontal pathogens and inflammation markers, which in turn reduce the progression of periodontitis.Conclusion: photodynamic therapy considered as promising, adjunctive and low-cost therapeutic method that is effective in tissue repair, reducing chronic periodontitis, reducing inflammation and is well-tolerated by patients.